Advances in informatics and computing in civil and construction engineering : proceedings of the 35th CIB W78 2018 Conference: IT in Design, Construction, and Management /: proceedings of the 35th CIB W78 2018 Conference: IT in Design, Construction, and Management. ([2019]) - Unknown
No abstract available